Rubber seed processing industry in India. Pt II. - Veeraputhran S; Joseph Toms
The cost of processing of rubber seed oil and cake in India is estimated using `split-off point' approach on the basis of the information collected from the processing units in the main processing centre of Virudhunagar district in Tamil Nadu. The properties of rubber seed oil and cake are explained along with hitherto reported commercial uses. In India Rubber seed oil is entirely consumed in the low quality soap manufacturing industry. Rubber seed cake is purchased mainly by the cattle rearers around the processing centres for direct feeding. The marketing of rubber seed oil and cake is explained along with a comparative analysis of the prices of comparable oils and cakes.
Keywords: India; Industrial application; Rubber seed processing